2007
DOI: 10.1007/s00011-006-6067-1
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of sleep abnormalities to chronic inflammatory conditions

Abstract: Sleep is vital to health and quality of life while sleep abnormalities are associated with adverse health consequences. Nevertheless, sleep problems are not generally considered by clinicians in the management of chronic inflammatory conditions (CIC) such as asthma, RA, SLE and IBD. To determine whether this practice is justified, we reviewed the literature on sleep and chronic inflammatory diseases, including effects of sleep on immune system and inflammation. We found that a change in the sleep-wake cycle is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
146
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(157 citation statements)
references
References 61 publications
8
146
0
3
Order By: Relevance
“…16 Recently emerging studies on sleep disturbance using validated sleep quality measures have suggested that those with quiescent IBD have greater sleep disturbance than healthy controls, and that poorer sleep was associated with lower IBD-related quality of life. 14,26 In our sample of community-based IBD patients, fatigue was highly prevalent for those with active disease, with almost three-quarters reporting significantly elevated levels. This is in contrast to only 5% of a healthy sample who reached similar levels of fatigue.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…16 Recently emerging studies on sleep disturbance using validated sleep quality measures have suggested that those with quiescent IBD have greater sleep disturbance than healthy controls, and that poorer sleep was associated with lower IBD-related quality of life. 14,26 In our sample of community-based IBD patients, fatigue was highly prevalent for those with active disease, with almost three-quarters reporting significantly elevated levels. This is in contrast to only 5% of a healthy sample who reached similar levels of fatigue.…”
Section: Discussionmentioning
confidence: 85%
“…13 Sleep disturbances have been associated with exacerbation of symptoms such as pain and fatigue in multiple chronic inflammatory conditions as well as worsening disease course. 14,15 Studies on fatigue in IBD have primarily relied on smaller samples (n<100), tertiary clinic recruitment, and patients with IBD in remission, 6,16 thereby considering only part of the spectrum of IBD presentation. The aim of this study was to evaluate fatigue and its related parameters more comprehensively, considering sleep quality, psychological factors, and biological indicators of inflammation and serum hemoglobin (Hg) levels simultaneously, in order to clarify their presentation and relationships in IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal sleep may exacerbate chronic inflammatory conditions [ 72 ]. It has also been proposed that management of poor sleep could be a non-invasive method to evaluate subclinical inflammation and may even play a role in keeping disease in remission [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uyku bozuklukları immün sistem fonksiyonlarında birtakım değişimlerle sonuçlanabilir. Sitokinler, konak immün fonksiyonu ve uyku uyanıklık siklusu arasındaki bağlantılara bakarak uyku bozukluğu, immünoenflamatuvar kaskatta kronik enflamatuvar durumla sonuçlanabilen bir rol oynayabilir 3 . Kronik enflamatuvar durumlarda uykunun rolü tam anlamıyla araştırılmamıştır.…”
Section: Introductionunclassified
“…Bu etkilerin mekanizması altta yatan immün sistem disregülasyonuna bağlı olabilir. Tüm bu noktaların ışığında kronik enflamatuvar durumların yönetiminde uyku bozukluklarının tedavisi göz ardı edilmemelidir 3 . Kronik enflamatuvar sürecin rol oynadığı psoriasis için kullanılan bazı yaşam kalitesi ölçümlerinde, uykuyla ilgili semptomlar sorgulanmasına rağmen bu konudaki çalışmalar oldukça sınırlıdır.…”
Section: Introductionunclassified